Real‐world effectiveness and safety of glecaprevir/pibrentasvir for the treatment of chronic hepatitis C infection: data from the German Hepatitis C‐Registry. Issue 8 (15th March 2019) - Berg, Thomas; Naumann, Uwe; Stoehr, Albrecht; Sick, Christoph; John, Christine; Teuber, Gerlinde; Schiffelholz, Willibold; Mauss, Stefan; Lohmann, Kristina; König, Bettina; Pangerl, Andreas; Niederau, Claus
Summary: Background: Glecaprevir/pibrentasvir is a pangenotypic direct‐acting antiviral regimen approved for treating adults chronically infected with hepatitis C virus (HCV). There are limited real‐world data on glecaprevir/pibrentasvir to date. Aim: To evaluate the effectiveness and safety of glecaprevir/pibrentasvir under real‐world conditions in the German Hepatitis C‐Registry (DHC‐R). Methods: The DHC‐R is an ongoing, non‐interventional, multicentre, prospective, observational cohort study that monitors patients with chronic HCV infection. Data were collected from patients who initiated glecaprevir/pibrentasvir and completed a screening visit on or after 2 August 2017. The primary effectiveness endpoint was sustained virological response at post‐treatment Week 12 (SVR12). Safety and tolerability were also assessed. Results: As of 15 July 2018, 586 patients received glecaprevir/pibrentasvir and had documented SVR12 data, treatment discontinuation, loss to follow‐up or HCV reinfection. Five hundred and fifty‐two patients (94%) received on‐label treatment. At baseline, most on‐label patients were infected with HCV genotype 1 (53%) or 3 (33%), HCV treatment‐naïve (90%), without cirrhosis (94%), and treated for 8 weeks (93%). Five hundred and thirty‐four patients (96.7%) achieved SVR12 (intention‐to‐treat [ITT] analysis). By modified ITT analysis (excluding patients who discontinued and did not achieve SVR12 or patients lost to follow‐up), the SVR12 rate was 99.4% (n/N = 534/537). There was one documented virological failure (relapse) and two documented HCV reinfections. One hundred and forty‐two (26%) adverse events (AEs) and 9 (2%) serious AEs occurred; 2 (<1%) AEs led to treatment discontinuation. All patients treated off‐label (N = 34) achieved SVR12. Conclusion: Glecaprevir/pibrentasvir was highly effective and well tolerated under real‐world conditions. Clinical trial number: DRKS00009717 (German Clinical Trials Register, DRKS).